Calcium-dependent Clustering of Inositol 1,4,5-Trisphosphate Receptors - Wilson, Bridget S. (The American Society for Cell Biology, 1998)
Rat basophilic leukemia (RBL-2H3) cells predominantly express the type II receptor for inositol 1,4,5-trisphosphate (InsP(3)), which operates as an InsP(3)-gated calcium channel. In these cells, cross-linking the high-affinity immunoglobulin E receptor (FcεR1) leads to activation of phospholipase C γ isoforms via tyrosine kinase- and phosphatidylinositol 3-kinase-dependent pathways, release of InsP(3)-sensitive intracellular Ca(2+) stores, and a sustained phase of Ca(2+) influx. These events are accompanied by a redistribution of type II InsP(3) receptors within the endoplasmic reticulum and nuclear envelope, from a diffuse pattern with a few small aggregates in resting cells to large isolated clusters after antigen stimulation. Redistribution of type II InsP(3) receptors is also seen after treatment of RBL-2H3 cells with ionomycin or thapsigargin. InsP(3) receptor clustering occurs within 5–10 min of stimulus and persists for up to 1 h in the presence of antigen. Receptor clustering is independent of endoplasmic reticulum vesiculation, which occurs only at ionomycin concentrations >1 μM, and maximal clustering responses are dependent on the presence of extracellular calcium. InsP(3) receptor aggregation may be a characteristic cellular response to Ca(2+)-mobilizing ligands, because similar results are seen after activation of phospholipase C-linked G-protein-coupled receptors; cholecystokinin causes type II receptor redistribution in rat pancreatoma AR4–2J cells, and carbachol causes type III receptor redistribution in muscarinic receptor-expressing hamster lung fibroblast E36(M3R) cells. Stimulation of these three cell types leads to a reduction in InsP(3) receptor levels only in AR4–2J cells, indicating that receptor clustering does not correlate with receptor down-regulation. The calcium-dependent aggregation of InsP(3) receptors may contribute to the previously observed changes in affinity for InsP(3) in the presence of elevated Ca(2+) and/or may establish discrete regions within refilled stores with varying capacity to release Ca(2+) when a subsequent stimulus results in production of InsP(3).